Analisis Yuridis Dampak Overcapacity Lembaga Pemasyarakatan terhadap Pembinaan Warga Lapas Ditinjau dari Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan: Studi Kasus Lapas Kelas II B Ende - Anjelina Wora Roi Wani; Daud Dima Tallo; Heryanto Amalo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the impact of the overcapacity of correctional institutions on the development of Class II Ende prison residents reviewed from Law No. 22 of 2022. This research uses a type of empirical juridical research by conducting field interviews with the Class II B Ende Prison and its Correctional Assisted Citizens, then conducting a study of literature materials by reading, studying, studying, and analyzing literature to develop an assessment related to the title of this thesis. The results of the study show that the impact caused by overcapacity affects the comfort of WBP due to congestion in residential spaces, affects the psychological well-being of WBP, the difficulty of WBP obtaining access to coaching in the independence development program, and also affects the level of security of WBP and Prison Officers, to overcome that the Class II B Ende Prison makes efforts by implementing matters related to regulations on coaching that stated in Law No. 22 of 2022 concerning Corrections, optimizing the effectiveness of alternative criminal penalties other than prison sentences and evaluating and continuing to develop coaching programs in prisons.